Decoding the Genetic Resources of Common Carp ( Cyprinus carpio ) Across Three Habitats in China: From Subspecies Patterns to Genetic Status - Xumeng He; Yang Gao; Jiamin Sun; Qigen Liu; Wenjing Hu (Fish and Fisheries, 2026)
As one of the earliest domesticated aquatic species, the common carp ( Cyprinus carpio ) has developed a dynamic and complex genetic landscape globally due to subspecies divergence, variety introductions and insufficient genetic management. China, which holds the world's largest diversity of both wild and domesticated carp populations, also faces substantial challenges in managing subspecies composition and genetic resources. In this study, 952 individuals from 25 populations across wild river systems, paddy fields and ponds were sampled, and mitochondrial DNA markers ( cytochrome b and control region) were used to redefine subspecies distributions from a habitat‐based perspective and to clarify genetic patterns within and among habitats. Our results show that C. c. rubrofuscus has become the dominant subspecies across all three habitat types, whereas C. c. carpio is mainly preserved in wild river populations in northeastern China. Pond populations retain the highest number of pure subspecies ( C. c. rubrofuscus and C. c. haematopterus ). Wild populations exhibited the highest genetic diversity and relatively low differentiation, while pond populations had the fewest haplotypes and the strongest genetic divergence, reflecting long‐term artificial selection. Paddy‐field populations displayed heterogeneous patterns: Qingtian, Heili and Qingyuan paddy‐field carp were highly isolated with low diversity, whereas others showed frequent gene flow with nearby wild carp. These findings highlight the need for habitat‐specific genetic management strategies to maintain genetic diversity and safeguard native carp resources.